Evaluation of the Validity of Student Interest Content in Learning Arabic Instruments Using the V Aiken Technique - Hidayah, Nurul; Ahmad, Ahmad; Parihin, Parihin (EDUPEDIA Publisher, 2025)
Purpose – This study aims to evaluate the content validity of an Arabic language learning interest questionnaire for fifth-grade students of Madrasah Ibtidaiyah, as interest is one of the key affective factors influencing student engagement and academic success, particularly in language learning. Methodology – The research employed a content validation design using the Aiken's V technique. The instrument consisted of 25 statement items assessed by three expert validators. Each item was rated using a five-point Likert scale to determine its relevance and clarity. The data were analyzed quantitatively using the Aiken's V formula to determine the degree of content validity. Findings – The analysis revealed that 21 items had moderate content validity (V ranging from 0.50 to 0.83), while 4 items demonstrated high content validity (V > 0.83). These results indicate that the questionnaire possesses acceptable content quality and can be considered a suitable preliminary tool for assessing students’ interest in learning Arabic. Novelty – This study contributes to the limited pool of validated instruments tailored specifically for assessing Arabic learning interest at the elementary Islamic school level in the Indonesian context. Significance – The findings are valuable for curriculum developers, Arabic language educators, and educational researchers seeking to understand better and measure students’ affective engagement. The study also lays the groundwork for further validation efforts involving construct validity and reliability testing.